Thailandina and Neothailandina and their family Thailandinidae salvaged: a valid taxonomic group of peculiar Permian fusuline Foraminifera. (March 2022) - Ueno, Katsumi
Abstract : The fusuline genera Thailandina Toriyama and Kanmera, 1968 and Neothailandina Toriyama and Kanmera, 1968 were established by Toriyama and Kanmera (1968) based on material from the Khao Phlong Phrab section of the Permian Rat Buri Limestone in central Thailand that is currently assigned to the Khao Khad Formation of the Saraburi Group (Ueno and Charoentitirat, 2011). These fusuline genera are peculiar in having parachomata and replaced tests by secondary mineralization. Moreover, Neothailandina was described to have a test with transverse septula, considered to be characteristic for Neoschwagerinidae. Based on these remarkable test features, Toriyama and Kanmera (1968) newly introduced the subfamily Thailandininae to accommodate these two new genera and assigned it to the Neoschwagerinidae, despite the lack of septula in Thailandina . Later, Kobayashi et al. (2010) argued that Thailandina and Neothailandina are just a mixed grouping of several known genera of schwagerinids, verbeekinids, and neoschwagerinids that are too altered by recrystallization to be recognizable, and rejected the taxonomic validity of these two genera as well as Thailandininae. The Khao Phlong Phrab section represents one of the standard late Cisuralian−Guadalupian (late early−middle Permian) fusuline successions in the eastern Paleotethys (Zhang and Wang, 2018) and contains not only Thailandina and Neothailandina but also abundant schwagerinid, verbeekinid, and neoschwagerinid fusulines (Toriyama, 1975; Fig. 1). I investigated the original specimens described by Toriyama and Kanmera (1968) and Toriyama (1975) from the section that are housed in the Department of Earth and Planetary Sciences of Kyushu University, Japan. I found that most of the grounds for Kobayashi et al.'s (2010) arguments to regard the thailandinin genera as taxonomically invalid are not supported by observations on these specimens as explained in the account that follows. In this taxonomic note, I propose that Thailandina and Neothailandina, and their family Thailandinidae, should be retained as valid taxonomic groups.